2013
DOI: 10.1155/2013/571372
|View full text |Cite
|
Sign up to set email alerts
|

Electroimpedance Spectroscopy for the Measurement of the Dielectric Properties of Sodium Chloride Solutions at Different Glucose Concentrations

Abstract: We investigated possible variations of impedance values in samples of sodium chloride solution (sodium chloride 0.9%) with glucose at different concentrations, ranging from 5000 to around 75 mg/dL. The sodium chloride solution (either saline physiological solution) was chosen since it has similarities to blood but no cell components, which may be confounding factors in this study. Special focus was on the effect of stirring and of temperature variations on the impedance spectrum of samples at different glucose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Last checked: 7/12/2012). Though in the studies [19-21] the correlation between conductivity and sodium concentration appears quite strong, simple conductivity measurement cannot completely guarantee highly accurate estimation of sodium concentration, due to the possible influence of several disturbing factors: namely, the other cations (potassium, calcium, magnesium), but also glucose, which proved to affect the impedance of a solution, though slightly, despite the fact that it does not decompose into ions [13, 14, 22-24]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Last checked: 7/12/2012). Though in the studies [19-21] the correlation between conductivity and sodium concentration appears quite strong, simple conductivity measurement cannot completely guarantee highly accurate estimation of sodium concentration, due to the possible influence of several disturbing factors: namely, the other cations (potassium, calcium, magnesium), but also glucose, which proved to affect the impedance of a solution, though slightly, despite the fact that it does not decompose into ions [13, 14, 22-24]. …”
Section: Discussionmentioning
confidence: 99%
“…We performed impedance measurement of the samples through a Solartron 1260 impedance analyzer (Solartron Analytical, UK), as already described in previous studies [13,14]. Through the Solartron 1260 we applied a 100 mV r.m.s.…”
Section: Methodsmentioning
confidence: 99%
“…Another perturbing factor is variation in temperature since electrical characteristic of tissue depends on tissue temperature. Change in impedance level with respect to temperature variations was explored in a study by measuring impedance of a solution consisting of sodium chloride and glucose at 1 MHz [168]. It was shown that increase in temperature from 32 • C to 42 • C make a reduction of about 22 Ω in impedance value of the sample.…”
Section: Patient Motion Artifacts Sweat/humidity and Temperature Flumentioning
confidence: 99%
“…In order to overcome this issue, electrochemical impedance spectroscopy (EIS) has to be carried out together with polarization curve measurements. EIS is a well-established technique for a complete analysis of electrochemical device behavior, but it has also been used in other fields of applied sciences in order to evaluate, for instance, the corrosion behavior of stainless steel [21] and different metallic alloys [22,23] at various operating conditions and in different media and even for biomedical applications [24].…”
Section: Introductionmentioning
confidence: 99%